2017
DOI: 10.1016/j.molmet.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Lipid nanoparticle delivery of glucagon receptor siRNA improves glucose homeostasis in mouse models of diabetes

Abstract: ObjectiveHyperglucagonemia is present in many forms of diabetes and contributes to hyperglycemia, and glucagon suppression can ameliorate diabetes in mice. Leptin, a glucagon suppressor, can also reverse diabetes in rodents. Lipid nanoparticle (LNP) delivery of small interfering RNA (siRNA) effectively targets the liver and is in clinical trials for the treatment of various diseases. We compared the effectiveness of glucagon receptor (Gcgr)-siRNA delivered via LNPs to leptin in two mouse models of diabetes.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 52 publications
(89 reference statements)
1
13
0
Order By: Relevance
“…In the first model, we treated diet-induced obese (DIO) mice with adeno-associated virus-8 (AAV8) in which short hairpin RNA targeting the glucagon receptor (sh-Gcgr) was driven by the H1 promoter, that silences genes in the liver 23, 30 . This treatment lowered hepatic Gcgr levels by ~80% (Figure 1A), and consistent with previous reports 31, 32 , it lowered fasting blood glucose levels from 189 ± 9 mg/dl to 142 ± 7 mg/dl (Figure 1B). Reduced hepatic Gcgr expression did not affect body weight or plasma insulin in the obese mice (Online Figure IA, B).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In the first model, we treated diet-induced obese (DIO) mice with adeno-associated virus-8 (AAV8) in which short hairpin RNA targeting the glucagon receptor (sh-Gcgr) was driven by the H1 promoter, that silences genes in the liver 23, 30 . This treatment lowered hepatic Gcgr levels by ~80% (Figure 1A), and consistent with previous reports 31, 32 , it lowered fasting blood glucose levels from 189 ± 9 mg/dl to 142 ± 7 mg/dl (Figure 1B). Reduced hepatic Gcgr expression did not affect body weight or plasma insulin in the obese mice (Online Figure IA, B).…”
Section: Resultssupporting
confidence: 91%
“…Various mouse models and human data have provided evidence that blocking glucagon action results in increased plasma LDL-C levels 13, 18, 31, 32 . While one study attributed this increase to elevated rates of lipogenesis, another report suggested that the mechanism is through an increase in intestinal cholesterol absorption 32, 60 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a LNP with tropism to hepatocytes delivered siRNAs targeting endolysosomal genes; this uncovered how Rab5 influenced endocytosis 9 . Similar approaches have been applied to hypertension 10 , heart disease 1113 , extracellular matrix signaling 14 , cancer 1516 , glucose homeostasis 17 , and other phenotypes 1819 . In addition to its utility as an in vivo scientific reagent, siRNA has treated disease in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we sought to knockdown Smad4 in type 2 diabetes with established kidney disease. In this model, hypertensive eNOS À/À mice on the C57BL/ 6J background are placed on a high fat diet (HFD) for 30 weeks with a single STZ injection on week 8 to further increase blood glucose levels to diabetic state while remaining hyperinsulinaemia, a characteristic of type 2 diabetes [19][20][21][22][23][24][25][26][27][28][29][30][31]. This regimen results in hyperglycaemia, hyperinsulinaemia, albuminuria, glomerulosclerosis and reduced kidney function ( Fig EV1).…”
Section: Resultsmentioning
confidence: 99%